2007
DOI: 10.1097/jto.0b013e3181560a68
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Ion Radiotherapy for Stage I Non-small Cell Lung Cancer Using a Regimen of Four Fractions during 1 Week

Abstract: Carbon ion beam radiotherapy with a regimen of four fractions during 1 week has been proven as a valid alternative to surgery for stage I NSCLC and to offer particular benefits, especially for elderly and inoperable patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
109
4
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 167 publications
(121 citation statements)
references
References 34 publications
(56 reference statements)
6
109
4
1
Order By: Relevance
“…The 2-year local control rate and OS were 93 and 89%, respectively, and the rate of radiation pneumonitis that was above grade 2 was only 4%. These results are comparable to that of a previous study of C-ion RT (8). However, additional follow-up is required to assess long-term outcomes and late adverse events following C-ion RT.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The 2-year local control rate and OS were 93 and 89%, respectively, and the rate of radiation pneumonitis that was above grade 2 was only 4%. These results are comparable to that of a previous study of C-ion RT (8). However, additional follow-up is required to assess long-term outcomes and late adverse events following C-ion RT.…”
Section: Discussionsupporting
confidence: 80%
“…For stage I NSCLC, a number of studies of C-ion RT revealed that its efficacy and safety were comparable to SBRT (8)(9)(10). Despite the high rate of local control in C-ion RT for stage I NSCLC, regional lymph node or distant metastasis are relatively common (8,9). Identifying patients with a high risk of metastasis is important and adjuvant chemotherapy may decrease the level of metastasis in these patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The carbon-ion therapy protocol, 52.8 GyE in 4 fractions, was defined according to the protocol used at the National Institute of Radiological Sciences in Chiba, Japan. 17 All radiation doses were delivered to the center of the tumor. All irradiation was given once a day, 5 days a week.…”
Section: Treatment Protocolsmentioning
confidence: 99%
“…The microscopic findings in our patient implied that the relapse pattern was marginal recurrence rather than infield recurrence, 4) even though a sufficient margin around the tumor had been set for the CIRT. While our single case is not enough for a discussion of the risk factors for local recurrence after CIRT, our case suggested that we should be careful while treating GGO lesions by radiotherapy.…”
Section: Discussionmentioning
confidence: 89%